Optimalisasi Laporan Penjualan Melalui Pelatihan Microsoft Excel Pada Bumdes Karya Maju Cemerlang Desa Apung Kecamatan Tanjung Selor Kabupaten Bulungan - Eri suparjan; Yuliana Ritna Bara; David Ifanly; Silva Septriana; Euis Hernawati; Dian Candra Fatihah; Candra Mecca Sufyana; Wiwi Warsiati (Journal on Education, 2024)
In an effort to achieve the welfare of village communities, BUMDes carries out its activities in accordance with the business potential that exists in the village. Village-Owned Enterprises (BUMDes) as business entities whose capital is wholly or largely owned by the Village have the obligation to manage assets, services and other businesses for the greatest welfare of the village community. One of the information needed by BUMDes is the presentation of financial information related to sales reports. One of the problems with recording sales is that it is still done manually, which is prone to recording errors which can make it difficult to calculate sales, this can disrupt BUMDes operations. Optimizing accurate sales reports using Microsoft Excel is the right choice, using this application will make the sales recording process more efficient and accurate. Microsoft Excel's various features, such as formulas and functions, make calculations easy and present sales reports in a neat and organized manner. So that recording errors can be reduced, operational efficiency can be achieved, and data reliability can be increased.